2019
DOI: 10.1111/ejss.12755
|View full text |Cite
|
Sign up to set email alerts
|

How green alternatives to chemical pesticides are environmentally friendly and more efficient

Abstract: Various soil management strategies that use disinfestation are important in the control of soil‐borne diseases before planting. However, only a few studies pay attention to preventing pathogen reinfestation during host plant cultivation, which is also important for the stable control of soil‐borne diseases. Here we used various pre‐planting management strategies to disinfest a field severely infested with Fusarium oxysporum, and then investigated changes in the potential pathogen and microbial communities duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…Collectively, autotoxic ginsenosides are capable of disrupting the equilibrium of soil fungal microbiota, principally through the stimulation of pathogenic taxa and the inhibition of beneficial taxa. It is well recognized that the winner of conflicts between phytopathogens and plant-beneficial microbes determines soil health and plant performance (7,40). Hence, further studies are still needed to investigate the impacts of the ginsenoside-induced fungal microbiota on plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, autotoxic ginsenosides are capable of disrupting the equilibrium of soil fungal microbiota, principally through the stimulation of pathogenic taxa and the inhibition of beneficial taxa. It is well recognized that the winner of conflicts between phytopathogens and plant-beneficial microbes determines soil health and plant performance (7,40). Hence, further studies are still needed to investigate the impacts of the ginsenoside-induced fungal microbiota on plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the involvement of microbes in pathogen suppression during RSD treatment, specific strains of Clostridia and Bacilli from treated soils could have a disease control effect [30,32]. The families Ruminococcaceae, Lachnospiraceae, and Clostridiaceae belonging to Clostridia increased during RSD and produced toxic compounds against plant pathogens [68][69][70]. Time-series analysis of soil microbiome and metabolome during RSD demonstrated that composition of Firmicutes abundance continuously changes throughout the treatment period and that population dynamics of Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…with an inverse proportion to the abundance of Fusarium (Huang et al, 2019), which may serve as a proxy to determine the risk probability of Fusarium diseases. Furthermore, the discovery of abundant Firmicutes in healthy soils (Liu and Zhang, 2021) agrees with our observation of abundant Bacillaceae (belonging to Firmicutes) in healthy soils.…”
Section: Community Variation Between Diseased and Healthy Roselle Rhizospheresmentioning
confidence: 99%